Towards improved solubility of poorly water-soluble drugs: cryogenic co-grinding of piroxicam with carrier polymers. (3rd March 2016) - Penkina, Anna; Semjonov, Kristian; Hakola, Maija; Vuorinen, Sirpa; Repo, Timo; Yliruusi, Jouko; Aruväli, Jaan; Kogermann, Karin; Veski, Peep; Heinämäki, Jyrki
Abstract: Amorphous solid dispersions (SDs) open up exciting opportunities in formulating poorly water-soluble active pharmaceutical ingredients (APIs). In the present study, novel catalytic pretreated softwood cellulose (CPSC) and polyvinylpyrrolidone (PVP) were investigated as carrier polymers for preparing and stabilizing cryogenic co-ground SDs of poorly water-soluble piroxicam (PRX). CPSC was isolated from pine wood ( Pinus sylvestris ). Raman and Fourier transform infrared (FTIR) spectroscopy, X-ray powder diffraction (XRPD) and differential scanning calorimetry (DSC) were used for characterizing the solid-state changes and drug–polymer interactions. High-resolution scanning electron microscope (SEM) was used to analyze the particle size and surface morphology of starting materials and final cryogenic co-ground SDs. In addition, the molecular aspects of drug–polymer interactions and stabilization mechanisms are presented. The results showed that the carrier polymer influenced both the degree of amorphization of PRX and stabilization against crystallization. The cryogenic co-ground SDs prepared from PVP showed an enhanced dissolution rate of PRX, while the corresponding SDs prepared from CPSC exhibited a clear sustained release behavior. In conclusion, cryogenic co-grinding provides a versatile method for preparing amorphous SDs of poorly water-soluble APIs. The solid-state stability and dissolution behavior of such co-ground SDs are to a great extent dependent on the carrier polymer used.